2021
DOI: 10.1002/ece3.8003
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic structure of the dwarf snakehead (Channa gachua) around Gulf of Tonkin: Historical biogeography and pronounced effects of sea‐level changes

Abstract: Geological events, landscape features, and climate fluctuations have shaped the distribution of genetic diversity and evolutionary history in freshwater fish, but little attention has been paid to that around the Gulf of Tonkin; therefore, we investigated the phylogeographic structure of the dwarf snakehead (Channa gachua) on Hainan Island and mainland China, as well as two populations in Vietnam. We attempted to elucidate the origins of freshwater fish in South Hainan by incorporating genetic data from DNA ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…The results of the millipede phylogenetic analyses appear to be explained by the geological timeframes of the formation of the Yangtze and Yellow rivers. Recent studies have indicated that large geographical barriers have an obvious blocking effect on genetic diversity and gene exchange within populations [ 52 , 53 , 54 ]. At present, the isolation of soil fauna in the Yangtze and Yellow rivers has not been extensively described, but some studies have shown that the Yangtze and Yellow rivers block the gene exchange of some terrestrial animals [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the millipede phylogenetic analyses appear to be explained by the geological timeframes of the formation of the Yangtze and Yellow rivers. Recent studies have indicated that large geographical barriers have an obvious blocking effect on genetic diversity and gene exchange within populations [ 52 , 53 , 54 ]. At present, the isolation of soil fauna in the Yangtze and Yellow rivers has not been extensively described, but some studies have shown that the Yangtze and Yellow rivers block the gene exchange of some terrestrial animals [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continental islands, due to their close proximity to neighboring continental areas, provide excellent opportunities for understanding the origin and diversification of freshwater fishes [ 1 ]. During glacial phases, the islands and the mainland were connected by land bridges due to the decrease in sea level.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the phylogeography of freshwater fishes between the island and mainland have focused on Taiwan and mainland China (e.g., Onychostoma barbatulus [ 3 ]; Squalidus argentatus [ 2 ]; Cobitis sinensis [ 4 ]; Opsariichthys [ 5 ]; Rhodeus ocellatus [ 6 ]; Acrossocheilus paradoxus [ 7 ]). There is relatively little information available on the phylogeography of freshwater fishes between Hainan Island and mainland China (e.g., Garra orientalis [ 8 ]; Aphyocypris normalis [ 9 ]; O. hainanensis [ 10 ]; Channa gachua [ 1 ]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations